STING-induced noncanonical autophagy regulates endolysosomal homeostasis - Tuozhi Huang; Chenglong Sun; Fenghe Du; Zhijian J. Chen (Proceedings of the National Academy of Sciences, 2025)
The cGAS–STING pathway mediates innate immune responses to cytosolic DNA. In addition to its well-established role in inducing inflammatory cytokines, activation of the cGAS–STING pathway also induces noncanonical autophagy, a process involving the conjugation of the ATG8 family of ubiquitin-like proteins to membranes of the endolysosomal system. The mechanisms and functions of STING-induced autophagy remain poorly understood. In this study, we demonstrated that STING activation induced formation of pH-elevated Golgi-derived vesicles that led to ATG16L1 and V-ATPase-dependent noncanonical autophagy. We showed that STING-induced noncanonical autophagy resulted in activation of the MiT/TFE family of transcription factors (TFEB, TFE3, and MITF), which regulate lysosome biogenesis. We found that lipidation of the ATG8 proteins, particularly GABARAPs, inhibited phosphorylation of MiT/TFE transcription factors by mTORC1. The lipidated GABARAPs bound to the Folliculin-interacting proteins (FNIPs), thereby sequestering the FNIP-folliculin protein complexes from activating mTORC1, resulting in dephosphorylation and nuclear translocation of MiT/TFE transcription factors. Furthermore, we found that STING-induced autophagy activated Leucine-rich repeat kinase 2 (LRRK2), a protein implicated in Parkinson’s disease, through GABARAPs lipidation. We further showed that STING-induced autophagy induced ALIX-mediated ESCRT machinery recruitment to mitigate endolysosomal perturbation. These results reveal the multifaceted functions of STING-induced noncanonical autophagy in regulating endolysosomal homeostasis.